Kinerja Biosensor Konduktometri Berbasis (Screen Printed Carbon Electrode) SPCE––Kitosan untuk Deteksi Diazinon, Malation, Klorpirifos dan Profenofos - Nuzulul Kurniawan Isvani; Ani Mulyasuryani; Sasangka Prasetyawan (Syarif Hidayatullah State Islamic University, 2015)
The performance of biosensor is based on the hydrolysis reaction of organophosphorus compounds catalyzed by organophosphate hydrolase (OPH), produce H+ and the other ionic species that increase conductance on the surface of electrode. In this research, OPH was immobilized by crosslinking on chitosan–glutaraldehyde membrane on the (Screen Printed Carbon Electrode) SPCE surface. Measurements were carried out at the range concentration 0 to 3.0 ppm of organophosphate, the range of pH 7.0 to 9.0 and 5–25 mL of enzyme. The result showed that optimum performances were obtained at 25 mL of OPH, pH 8.5, with the sensitivity for dizinon, malathion, chlorpirifos and profenofos is 1.353 mS/ppm, 1.270 mS/ppm, 1.230 mS/ppm dan 1.77 mS/ppm respectively and 0.97; 1.03; 0.98; 0.97 of LOD. DOI :http://dx.doi.org/10.15408/jkv.v0i0.3156.